The Impact of Character Education on High School Students' Social Ethics and Responsibilities: A Systematic Literature Review of Scopus-Indexed Articles - Ulya Nur Izzatun Nimah; Mohammad Zakki Azani; Istanto Istanto (Universitas Muhammadiyah Surakarta, 2025)
Character education plays a crucial role in shaping students' social ethics and responsibilities, particularly within the context of school education. This systematic literature review analyzes studies from Scopus-indexed journals to assess the impact of character education on the development of moral values such as honesty, discipline, and responsibility among high school students. The review highlights various character education models, especially those grounded in religious values like Islam, which have shown positive effects on students' ethical behavior and social responsibility. Research indicates that schools implementing character education programs report significant improvements in students' social behaviors, such as increased pro-social actions and a reduction in negative behaviors. However, the implementation of such programs faces several challenges, including a lack of teacher training, limited relevant instructional materials, and difficulties integrating religious teachings into subjects like science and mathematics. Additionally, cultural diversity and time constraints are significant barriers to effective implementation. Despite these challenges, the empirical evidence suggests that when schools integrate character education effectively, it not only enhances students' academic performance but also fosters responsible, ethical individuals. The review also proposes strategies to overcome these challenges, emphasizing the importance of teacher training, curriculum integration, and the collaboration between schools, families, and communities. This study aims to provide a comprehensive understanding of how character education influences student ethics and responsibility and offers policy recommendations for enhancing its effectiveness in schools worldwide.